PENDIDIKAN KARAKTER MELALUI KEMITRAAN FULL DAY SCHOOL ANTARA SEKOLAH UMUM DAN MADRASAH DI PASURUAN - Saidah, Saidah; Zakiatul Munawaroh (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
This study aims to describe the implementation of character education through a Full Day School partnership program between public schools and madrasahs in Pasuruan. The background of this research lies in the need for synergy between general and religious educational institutions in shaping students' character holistically. This research employs a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the partnership successfully integrates the national curriculum with religious values and local wisdom in full day learning activities. The character education developed includes values such as religiosity, responsibility, discipline, tolerance, and cooperation. Furthermore, support from parents and the community strengthens the implementation of the program. The conclusion of this study is that the partnership between public schools and madrasahs through the Full Day School model in Pasuruan serves as an effective strategy for enhancing students’ character development.